Perilaku Petani terhadap Risiko Usatahani Padi Sawah di Desa Puasana Kecamatan Amonggedo Provinsi Sulawesi Tenggara - Abdullah, Weka Gusmiarty (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2011)
Risk and uncertainty were agriculture’s characteristics, especially rice farming. Therefore a farmer must be sure in behavior toward the risk and uncertainty in farming. There were three kinds of risk behavior, namely: risk lovers, risk-averse, and risk neutral. The aims of this research were : (1) to analyze the risk behavior of wet rice field farmer, and (2) to determine social economic factors that influence the risk behavior of wet rice field farmer. Simple random was implemented in sampling method to get about 67 wet rice field farmer. Quadratic utility function analysis and multiple linear regression analysis were implemented in this research. Research findings show that almost wet rice field farmer has risk neutral behavior, namely 62.7%. There were 19.4% wet rice field farmer by the risk lovers behavior, and the remain 17.9% wet rice field farmer have risk-averse behavior. The risk behavior of the wet rice field farmer was influenced by age, a total of family duties, land area, and family labor. The increasing of farmer’s age and a total of family duties will increase the farmer’s loves to his farm risk, while the increase of family labor and the land area will increase the farmer’s averse to his farm risk.